Organisational Learning and Competitive Advantage of Media Broadcasting Organisation in Rivers State (Global Journal of Management and Business Research, 2020)
The relationship between organisational learning and competitive advantage of media broadcasting organisations in Rivers State was the focus of this study. We used survey research design and the research instrument used was questionnaire. The study population was made up of three media organisations staff in Rivers State. The population was 1405 staff and using Krejcie and Morgan sample size determining table was used in determining our sample size and we had 302 staff as sample size. Random sampling method was used in administering the questionnaire on our respondents and Pearson Product Moment Correlation was the tool applied in testing the hypotheses. It was revealed in the findings that there exist relationship amongst organisational learning and competitive benefit of media broadcasting organisations in Rivers State.
Keywords: organisation; differentiation; organisational learning; competitive advantage